Economic effects of recent social and technological developments - Florian W. Bartholomae (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2017)
This paper summarizes and connects the main findings of the habilitation project. The important social developments analyzed, result from the demographic change that many economies will face in the future. Especially on the regional level, problems arise due to increasing disparities in population. This challenges the comprehensive pro-vision of public services such as health care or basic infrastructure. Therefore, new strategies have to be implemented and previous structures have to be adapted. In particular, as also many cities, which have always been agglomeration areas of economic activity, face demographic and/or economic problems, appropriate proactive strategies must be developed to ensure future prosperity. The most predominant recent technological development is the emergence and comprehensive availability of the Internet. This has led to new business opportunities but also new threats for economic activity. One particular online market comprises online games. In this market, due to the virtuality on the one hand and the importance of net-work externalities on the other hand, challenges for the assignment of property rights of virtual objects and optimal pricing strategies arise that have to considered. In the context of B2B, and also B2C, cloud computing becomes more and more important, however, this service is threatened by cybercriminals that force access into the cloud. Thus, the provider must develop strategies to prevent damage for his customers and the economy. All in all, overall analysis shows that only cooperation of all relevant (economic) stakeholders can help to overcome challenges of social and technological developments.
Keywords: D9; H7; K4; L1; L86; O1; O3; R1; 330